2019
DOI: 10.3892/ol.2019.10301
|View full text |Cite
|
Sign up to set email alerts
|

Chidamide, a histone deacetylase inhibitor, induces growth arrest and apoptosis in multiple myeloma cells in a caspase‑dependent manner

Abstract: Chidamide, a novel histone deacetylase (HDAC) inhibitor, induces antitumor effects in various types of cancer. The present study aimed to evaluate the cytotoxic effect of chidamide on multiple myeloma and the underlying mechanisms involved. Viability of multiple myeloma cells upon chidamide treatment was determined by the Cell Counting Kit-8 assay. Apoptosis induction and cell cycle alteration were detected by flow cytometry. Specific apoptosis-associated proteins and cell cycle proteins were evaluated by west… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 45 publications
0
40
0
Order By: Relevance
“…This data provides evidence of HDACi capability of restoring acetylation levels in an in vitro model of RSTS, strongly pointing to tailored future perspective in accordance with the idea of personalized medicine. We also evaluated the cytotoxicity of selected concentrations, given that HDACi are also used in oncological trials for their ability to induce selected and dose-dependent apoptosis (De Schutter and Nuyts, 2009;Yuan et al, 2019). Importantly, we did not observe neither an increase in cell death nor a decrease in cell proliferation, indicating that HDACi can boost acetylation at sub-toxic concentration in our in vitro modelling system.…”
Section: Discussionmentioning
confidence: 91%
“…This data provides evidence of HDACi capability of restoring acetylation levels in an in vitro model of RSTS, strongly pointing to tailored future perspective in accordance with the idea of personalized medicine. We also evaluated the cytotoxicity of selected concentrations, given that HDACi are also used in oncological trials for their ability to induce selected and dose-dependent apoptosis (De Schutter and Nuyts, 2009;Yuan et al, 2019). Importantly, we did not observe neither an increase in cell death nor a decrease in cell proliferation, indicating that HDACi can boost acetylation at sub-toxic concentration in our in vitro modelling system.…”
Section: Discussionmentioning
confidence: 91%
“…HDACi are tested in oncology trials for their ability to stop tumor cell proliferation by inducing selected and dose-dependent apoptosis [ 34 ]. Thus, our observation that selected HDACi dosing does not modulate cell proliferation or death in RSTS cells indicates that HDACi can boost acetylation at a sub-toxic concentration, at least in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that chidamide has anti-tumor effects in a variety of hematological malignancies (such as lymphoma, myeloma, and leukemia)[ 22 ]. Many studies have confirmed the anti-myeloma effect of chidamide, and it mainly promotes the G0/G1 arrest and apoptosis of G0/G1 in a caspase-dependent manner in myeloma cells[ 23 ]. We herein reported the results of a highly successful treatment for the diagnosis of pPCL 5 years ago.…”
Section: Discussionmentioning
confidence: 99%